The Integration of the Information and Communication Technology at Primary School in Tunisia: A Hope or a Project - Bahloul, Mourad; Monin, Noelle; Khecharem, Sami (Global Journal of Educational Studies, 2024)
Digital education is one of the most important tools that should be employed in the normal situation in all societies because of its role in facilitating the learning environment and the education process. Currently, with the spread of the Corona virus epidemic, all educational institutions, including schools, universities and scientific institutes, have been closed in an emergency and sudden manner which has made it necessary for educational institutions to search for new and innovative ways and methods for the continuity of the educational process. The best way to achieve this is to resort distance education which many universities and scientific institutes were able to use and became required by this emergency situation. But were these institutions are have been prepared for this sudden use of digital education tools? Did they perform their role? Are the teachers and students ready for this major and qualitative change in education? This article offers an analysis of the use of information and communication technology in primary school in Tunisia between theory and practice. The research showed that the teachers in our sample are not attracted by digital culture in their teaching practices because they have not acquired techno-pédagogical skills that allow them to script and evaluate learning via digital technology and they don’t receive a real support from pédagogical team.